Farmers' Knowledge Is the Basis for Local Level Agro-Forestry Management: The Case of Lemo Woreda in Hadiya Zone, Ethiopia - Horamo, Yohannes; Chitakira, Munyaradzi; Yessoufou, Kowiyou (Frontiers in Sustainable Food Systems, 2021)
Agroforestry is a traditional practice that sustains rural farmers for generations. This is because of the ecological and economic benefits inherent to the systems. However, due to several challenges, e.g., climate change, shortage of lands, soil erosion and pollution, etc., the practice has increasingly been abandonned in some rural areas, e.g., the Lemo Woreda in Ethiopia. If this trend continues, effective knowledge on an important agricultural system may be lost in a near future. In the present study, the aim is to investigate and document farmers’ traditional knowledge of managing agroforestry. Data were collected through semi-structured interviews conducted in six villages from three peasant associations (PAs). In total, 73 households were selected for interview and the data collected on farmers knowledge were analysed using SPSS (Statistical Package for Social Science) version 26. Our results revealed, according to local farmers knowledge, tree species that contribute to crop yield improvement and the important role agroforestry trees play with regard to soil fertility. Farmers’ strategies to associate trees and shrubs in their farmlands were revealed. Tree species with a negative effect on crop yields were also reported by farmers. Farmers reported and ranked in the order of importance, agro-forestry opportunities and challenges that need to be addressed if we are improve current traditional agroforestry practices to meet future challenges (environmental degradation, pollution, population growth, etc.). We strongly recommend that active research programs be developed to document traditional agroforestry knowledge that are rapidly disappearing. Such knowledge documentation is necessary to inform development projects that require the buy-in of local farmers.